Piper betle L. and Persicaria odorata (Lour.) Soják as alternative to antimicrobial growth promoters in broiler chickens - Muhammad, Abdul Basit (2021)
In several countries, except Europe, dietary supplementation of sub-therapeutic antimicrobial growth promoters (AGPs) is commonly practised for sustainable broiler chicken production. However, their indiscriminate use resulted in antibiotic resistance, which leads to a ban against AGPs. Hence, it is essential to find potential and safe alternatives that can improve broiler chickens' production performance. Recently, phytobiotics, especially herbs, have gained attention and have been extensively studied for their possible use as an alternative poultry feed additive. Generally, phytobiotics are assumed to be natural, safe, and residue-free substances; however, scarce literature is available about their optimal dosage and safe use. The present study was carried out to assess the phytochemical screening, quantification of secondary metabolites, acute oral toxicity, appropriate dosage and potential of selected herbs Piper betle and Persicaria odorata as alternative growth promoters to AGPs in broiler chickens. P. betle and P. odorata leaf extracts were evaluated for qualitative and quantitative phytochemical screening, antioxidant and antimicrobial potential. The preliminary phytochemical analysis of P. betle and P. odorata leaf extracts revealed the presence of flavonoids, phenols, saponins, tannins, glycosides, and volatile oils. The higher total phenolic content and total tannins were quantified from P. betle methanolic leaf extract. Additionally, it showed increased antioxidant activity compared to P. odorata leaf extracts. The in vitro antibacterial potential of both herbs was estimated against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Salmonella enterica, Pseudomonas aeruginosa, Candida albicans, and Aspergillus brasiliensis. The methanolic leaf extract of Piper betle showed antibacterial and antifungal activity against selected strains. In conclusion, phytochemical screening of P. betle and P. odorata leaf extracts showed rich diversity of phytochemicals, antioxidant, and antimicrobial activity. In the first phase, quantitative phytochemical analyses of methanolic extract of P. betle and P. odorata was carried out using chromatography. Furthermore, the limit dose acute toxicity of the selected herbs was estimated in broiler chickens according to the guidelines of OECD, 2016. A total of 35 broiler chicks were used in this study. On day 21 of age, the chicks were randomly allocated into 7 treatment groups. The birds in extract-treated groups were orally gavaged with a single dose of methanolic leaf extract of P. betle and P. odorata at the rate of 500mg/kg, 1000 mg/kg, and 2,000 mg/kg, respectively. At the same time, the control group received 0.5% carboxymethyl cellulose (CMC) as a placebo. The gas chromatography-mass spectrometry (GC-MS) fingerprints showed the presence of various metabolites. Furthermore, the secondary bioactive compounds eugenol and quercetin were successfully quantified from P. betle and P. odorata, respectively. Acute toxicity study has shown no behavioural or physical changes in the chickens of treated groups. There were no significant differences in growth performance, haematological indices, serum biochemistry, and relative internal organs weights between the control and extract treated groups. The gross and microscopic observations indicated no changes in the liver, heart, lungs, spleen, gizzard, and kidneys of the treated birds. In conclusion, secondary bioactive compounds eugenol and quercetin were successfully quantified from methanolic leaf extract of P. betle and P. odorata. Based on current study results, the LD50 value for the tested extracts would be > 2000 mg/kg body weight. The second phase was conducted to estimate the influence of different dose supplementation of Piper betle leaf meal (PBLM) and Persicaria odorata leaf meal (POLM) on growth performance, ileal digestibility, gut morphology, haematological indices, serum biochemical attributes, histomorphology of the liver, and internal organs parameters in broiler chickens. A total of 210 day-old broiler chicks were fed either basal diet (BD) or BD + 2, 4, and 8 g/kg of PBLM and POLM. Except for PBLM 8g/kg, graded dose inclusion of PBLM and POLM increased (p < 0.05), the body weight gain (BWG) positively modulated the gut architecture and enhanced nutrient digestibility in broiler chickens. Birds fed on PBLM 4g/kg and POLM 8g/kg had significantly higher (p < 0.05) BWG with superior (p < 0.05) feed efficiency. Haematological indicators like red blood cells and haemoglobin were positively improved in birds fed on diet PBLM 4g/kg and POLM 8g/kg compared to the control group. Additionally, dietary supplementation of PBLM and POLM decreased the activity of AST and ALT with reduced serum concentration of triglyceride and cholesterol, which were observed lowest in PBLM 4g/kg and POLM 8g/kg groups. On the other hand, the serum concentrations of total protein (TP), albumin, and globulin were recorded as increased (p < 0.05) in broilers raised on the diets PBLM 4g/kg and POLM 8g/kg. Notably, dietary supplementation of PBLM and POLM did not influence the organ parameters and showed no adverse effects on liver histomorphology. In conclusion, dietary supplementations of phytobiotics (PBLM 4 g/kg and POLM 8 g/kg) positively modulated the intestinal microarchitecture with enhanced nutrient digestibility. Hence, it resulted in maximum body weight gain with improved haematological indicators and serum biochemistry attributes. Furthermore, dietary supplementations of phytobiotics have no deleterious effects on the internal organs and retained relatively normal hepatic parenchyma, thus enhanced the optimum growth performance of the broiler chickens. The third phase experiment was designed to estimate the comparative efficacy of PBLM and POLM with AGPs on growth performance, gut morphology, ileal digestibility, caecal microbiota composition, tibial bone morphometry, and meat quality in broilers chickens. Based on the earlier trial results, PBLM 4g/kg and POLM 8g/kg were selected for the comparative efficacy study. A total of 150 day-old broiler chickens were fed basal diet (BD), which served as the negative control (NC) or BD + 0.2g/kg tetracycline as positive control (PC); BD + 0.03g/kg halquinol (HAL), BD + 8g/kg POLM (Po8), and BD + 4g/kg PBLM (Pb4) as treatment groups. Dietary supplementation of phytobiotics Po8 and Pb4 showed improved growth performance, positively modulated the gut architecture, and improved digestibility comparable to AGPs. Additionally, dietary supplementation of phytobiotics (Po8 and Pb4) significantly decreased the E. coli, Salmonella, and Staphylococcus aureus compared to the NC group. However, supplementation of Pb4 resulted in significantly decreased total anaerobic bacteria and Clostridium counts compared to the NC group. Importantly, dietary supplementation of phytobiotics significantly increased the Lactobacillus count compared to HAL, PC, and the NC groups. The supplementation of phytobiotics improved meat quality compared to the NC group. Moreover, significantly (p < 0.05) higher values of geometric parameters of tibial bones with increased strength were recorded in chickens fed on the phytobiotics, compared to the NC group. Conclusively, phytobiotics showed performance comparable to the selected AGPs. The present study results provided evidence that the dietary supplementation of PBLM 4 g/kg and POLM 8 g/kg are the appropriate and safe doses. PBLM and POLM could be the potential alternatives to AGPs for sustainable broiler chicken production.